Ber Performance of Ofdm-Based Visible Light Communication Systems - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper, OFDM-based techniques designed for Intensity Modulation/Direct Detection (IMDD) modulation applied to Visible Light Communications (VLC) systems are evaluated. The evaluated techniques are Asymmetrically Clipped Optical OFDM (ACO-OFDM), Direct Current (DC) Biased Optical OFDM (DCO-OFDM), and Asymmetrically Clipped DC Biased Optical OFDM (ADO-OFDM). These techniques are evaluated and compared for different types of M-QAM modulation in terms of Bit Error Rate (BER). It is shown that ACO-OFDM, in general terms, presents a better performance compared to the conventional DCO-OFDM and ADO-OFDM schemes. © 2019 IEEE.